EVALUATING ARABIC LANGUAGE EDUCATION BASED ON THE FOUNDATIONS OF MULTIPLE INTELLIGENCES BY HOWARD GARDNER - Husna, Wardiyatul; Waro, Ruhamaul; Chamidah, Dewi (Abjadia : International Journal of Education, 2024)
This research was conducted based on problems that occurred in Indonesia where the form of evaluation to find out student learning outcomes is only based on intellectual intelligence and does not include multiple intelligences as a whole. So that the resulting scores can be said to be invalid by looking at the diverse intelligence backgrounds of students. Therefore, the researcher seeks to provide an overview of the form of the question through this paper. Teachers can use the form of questions according to the diverse intelligence of students with the aim of validly measuring student learning outcomes. This research aims to develop an assessment for learning the Arabic language based on the multiple intelligences initiated by Howard Gardner. This study uses a qualitative approach with desk research type. This research consists of identifying literature sources, collecting data, analyzing data, verifying and interpreting, and drawing conclusions. The results of the study show that assessing Arabic language learning based on multiple intelligence should not only be done with tests, but also with non-test activities. Because the assessment in the form of tests includes only linguistic and logical-mathematical intelligence, as well as visual-spatial intelligence. As for other intelligences, it is possible to conduct assessments in the form of tests other than tests. Apart from intellectual intelligence, there is also emotional intelligence and spiritual intelligence. The scores resulting from the evaluation of these two intelligences are included in the evaluation of students' attitudes.